Formulation and Evaluation of 1 mg Alprazolam Tablet - Mutiawati, Yuti; Rusdiana, Taofik; -, Fitrileni; Khorunisa, Anis (Indonesian Journal of Pharmaceutical Science and Technology, 2014)
Alprazolam is benzodiazepines drug which used to manage short-term anxiety disorder, also used for the treatment of panic disorder, with or without agographobia. Many factors can affect drug dissolution rates from tablets, hence possibly drug bioavailability- including the crystal size of the drug, tablet disintegration mechanisms and rates, the method of granulation, type and amount of granulating agent employed, type, amount and method of incorporation of disintegrants and lubricants and other formulation and processing factors. The aim of the study was to prepare and evaluate alprazolam tablets with dosage strengths 1 mg, with wet granulation method, as an adjuvant used: corn starch and lactosa sebagai filler, sodium lauril sulfat as solubilizer, sodium starch glycolat as desintegrant,Â Erytrocin CI 45430 as colloring, polivinyl pirolidon K 30 as binder with variatrion concentration, ethanol 95% as wetting agent, talc, silicon dioksida coloidal and magnesium stearat as glidant and antiadherent, test for the granule are particle distribution, water content, angle of repose, bulk density, taped density, apparent density (compressibility), and test for the tablet dosage are description of tablet, wight uniformity, hardness, desintegration time, content uniformity, disolution, for the selected formula tested the comparison of disolution and bioequivalence to 1 mg Alprazolam tablet innovator, the results obtained, that the tablet alprazolam 1 mg, are meet the requirements.Â Keywords:Â Alprazolam, bioequivalence test, dissolution comparison test